1990
DOI: 10.1002/1097-0142(19901101)66:9<1949::aid-cncr2820660917>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone acetate lowers plasma corticotropin and cortisol but does not suppress anterior pituitary responsiveness to human corticotropin releasing factor

Abstract: The endocrine action of medroxyprogesterone acetate (MPA) has been claimed to be of a glucocorticoid‐like nature. Upon clinical observation, MPA has been shown to improve life quality and overall well‐being in patients with advanced breast cancer, renal carcinoma, prostatic carcinoma, and uterine adenocarcinoma. The authors have evaluated MPA endocrine action by the administration of human corticotropin releasing factor (hCRF) in a 90‐minute assay in 15 patients with advanced breast cancer or renal cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…Although MPA does bind to the glucocorticoid receptor at one tenth of the potency as the synthetic glucocorticoid, dexamethasone (Pridjian et al 1987), and at high doses has been shown to curb the stress response seen in cancer patients (Lang et al 1990), in the current report the working memory load effect lends support to the hypothesis that MPA modulates memory, specifically. The nature of the working memory load in the radial-arm maze is such that the only aspect that changes across trials is the memory demand and not the motivator involved.…”
Section: Discussionsupporting
confidence: 54%
“…Although MPA does bind to the glucocorticoid receptor at one tenth of the potency as the synthetic glucocorticoid, dexamethasone (Pridjian et al 1987), and at high doses has been shown to curb the stress response seen in cancer patients (Lang et al 1990), in the current report the working memory load effect lends support to the hypothesis that MPA modulates memory, specifically. The nature of the working memory load in the radial-arm maze is such that the only aspect that changes across trials is the memory demand and not the motivator involved.…”
Section: Discussionsupporting
confidence: 54%
“…Our previous ACTH and cortisol pulsatility studies in normal female volunteers had all been performed in the follicular phase of the menstrual cycle, but there are many theoretical reasons why ACTH levels may be different at different times during the menstrual cycle. Both oestrogens and progesterone may alter ACTH and cortisol secretion through a variety of mechanisms including changes in cortisol binding globulin (Sandberg & Slaunwhite, 1959), a direct glucocorticoid agonist action of progesterone (Lang et al, 1990), and altered cortisol metabolism (Murphy, 1981;Baggia et al, 1990). Whatever mechanism predominates, we did observe a significant reduction in both 12-hour mean and AUC plasma ACTH levels in the luteal phase of the cycle, when serum progesterone concentrations were all above 63 nmol/l.…”
Section: Discussionmentioning
confidence: 59%
“…The presence of the oestrogen receptors in the mouse cochlea seems to provide a neuroprotective effect against acoustic trauma (Meltser et al, 2008). Specific progesterone receptors have not been identified in the cochlea, but progesterone may cross-react with other steroid receptors present in the cochlea or more proximal areas of the auditory system (Lang et al, 1990;Nathan et al, 1999). Progesterone and its metabolites are known to interact with the steroid binding sites on gaminobutyric acid-A receptors (GABA-A), which are present throughout the auditory system, leading to a rapid modulation of central nervous system (CNS) excitability (Majewska et al, 1986;Follesa et al, 2001).…”
Section: The Ovarian Hormones and Auditory Functionmentioning
confidence: 99%